Factors that intervene in students oral language proficiency when learning english and french at the same time after the completion of the sixth terms of the development area subjects, semester I-2017, in the Modern Languages major at The Foreign Languages Department of The University of El Salvador. - Polanco Fuentes, Claudia Nineth; Cabrera Alvarenga, Santos Isaac (2024)
The University of El Salvador offers the Modern Languages Major: Specialty in French and English since 2002. Currently, there are 1,0351 active students not only from the San Salvador area but also from different regions of the country as well. It caught the researchers’ attention the fact that many of the students present difficulties when developing the necessary oral linguistic abilities to succeed in the acquisition of a second language. Therefore, this research focused on the factors that intervene in students’ oral language proficiency when learning English and French at the same time after the completion of the sixth term of the skills development area subjects, Semester I-2017, in the Modern Languages Major at the Foreign Language Department of the University of El Salvador. This study was focused on discovering which factors intervene in students’ oral language proficiency when learning English and French at the same time, identifying the most important ones, during the teaching-learning process and their contribution to the success or failure of the complete assimilation of the two languages. A certain number of surveys were filled out by Modern Languages students, on semester I-2017, that were taking their term VII of the Major and that have successfully completed the sixth term of the development area subjects in English and French. In addition, interviewing teachers was necessary to get more information about the factors that intervene in students’ oral language learning proficiency, since teachers have an important role for students when they learn a second language. These interviews provided a better understanding of what happens inside the classroom and a wider opinion about the oral proficiency was obtained. Finally, a standardized English and French oral format evaluation was applied to measure students’ oral proficiency, in order to confirm the gathered information acquired from the students surveys.